Description of a new montane freshwater crab (Crustacea: Potamidae: Geothelphusa) from northern Taiwan - Shy, Jhy-Yun; Shih, Hsi-Te; Mao, Jean-Jay (Zootaxa, 2014)
A new freshwater crab is described from a montane area in northern Taiwan based on morphological characters and molecular evidence. Geothelphusa cilan sp. nov., from the Cilan Forest, situated on the boundary of Hsinchu and Yilan (= Ilan) counties, is close to G. monticola Shy, Ng & Yu, 1994, and G. takuan Shy, Ng & Yu, 1994, but can be distinguished by its male first gonopod (G1) and the ratio of thoracic sternites. Molecular evidence from mitochondrial cytochrome oxidase subunit I (COI) also supports the identity of the new species.